2008
DOI: 10.2353/ajpath.2008.070623
|View full text |Cite
|
Sign up to set email alerts
|

Endosialin (Tem1) Is a Marker of Tumor-Associated Myofibroblasts and Tumor Vessel-Associated Mural Cells

Abstract: Tumor progression and metastasis are critically dependent on the tumor stroma consisting of fibrous connective tissue, newly formed blood vessels, extracellular matrix, and recruited inflammatory cells. Tumor stromal fibroblasts (activated fibroblasts or myofibroblasts) acquire a specific phenotype that differentiates them from normal resting fibroblasts. They express smooth muscle actin (SMA), and isolated myofibroblasts have higher proliferation rates than their normal counterparts.1 The importance of stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
149
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 26 publications
10
149
2
Order By: Relevance
“…Thus, the presence of CD248 within cells leads to an increase in proliferation, which interestingly was more pronounced at higher cell densities. These data are consistent with the previous in vitro studies which suggested a role for human CD248 in regulating proliferation, migration and adhesion to fibronectin, as well as sensing an increase in cell density [7,18].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the presence of CD248 within cells leads to an increase in proliferation, which interestingly was more pronounced at higher cell densities. These data are consistent with the previous in vitro studies which suggested a role for human CD248 in regulating proliferation, migration and adhesion to fibronectin, as well as sensing an increase in cell density [7,18].…”
supporting
confidence: 93%
“…It is a member of an emerging transmembrane protein family implicated in tissue remodelling and repair, which includes CD141 and CD93 [2,3]. CD248 is expressed on fibroblasts and pericytes during development and in tumour-associated stroma [4][5][6][7]. An important role for CD248 within tumour stroma has been highlighted in CD248-deficient mice; abdominal tumours implanted into mice lacking CD248 demonstrated reduced growth, invasion and metastasis [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent data, endosialin is preferentially associated with pericytes and stromal fibroblasts, but not with endothelial cells, as suggested in earlier studies (MacFadyen et al, 2005;Christian et al, 2008;Simonavicius et al, 2008). Pericytes form an outer sheath around the endothelium and play an important role in maturation of blood microvessels and stabilisation of vascular network, whereas stromal fibroblasts stimulate angiogenesis by trophic effects and extracellular matrix reorganisation (Jain, 2003;Armulik et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
“…Thus, to exploit both passive and active targeting potentials, we engineered SHK-loaded PEGylated PLGA NPs decorated with anti-TEM1 Ab/scFv. TEM1 has been reported to be expressed by the endothelial cells of ovarian tumor vasculature 25,[44][45][46][47] and other malignancies such as brain and abdominal tumors. 48,49 Based on the release profile, less than 20% of drug can be released within 2 hours, during which the engineered NPs can safely pass the blood stream and reach the target site with negligible inadvertent detrimental impacts on blood-circulating immune system cells.…”
mentioning
confidence: 99%